1966
DOI: 10.2307/1942153
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Studies of Funaria hygrometrica Hedw. in Eastern Washington and Northern Idaho

Abstract: Fra. 1. Funaria in relation to the vascular vegetation. Solid dots = locations where the plant was collected. Circle = location of nursery where experiments were carried out. X 's = locations where observations were made on burned areas. Vegetation zone data from Daubenmire (1942, 1952).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 55 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…These controls can comprise nutrients, pH, photoperiod and exogenous substances (Grime et al, 1981;Hölzel and Otte, 2004;Glime, 2007). For instance, the weed moss species Funaria hygrometrica is known to show better spore germination and protonemal growth on soil from burned areas, which are phosphate-nitrate enriched (Hoffman, 1966;Esposito et al, 1999). Nitrate is the major naturally occurring inorganic soil component that stimulates seed and fern spore germination (Hilhorst and Karssen, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These controls can comprise nutrients, pH, photoperiod and exogenous substances (Grime et al, 1981;Hölzel and Otte, 2004;Glime, 2007). For instance, the weed moss species Funaria hygrometrica is known to show better spore germination and protonemal growth on soil from burned areas, which are phosphate-nitrate enriched (Hoffman, 1966;Esposito et al, 1999). Nitrate is the major naturally occurring inorganic soil component that stimulates seed and fern spore germination (Hilhorst and Karssen, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that inoculation material should be mass-produced by vegetative regeneration with rapid development (Jones and Rosentreter, 2006;Mishler, 1988) because of the need for moss biocrusts to inoculate large areas. The factors that influence the tissue cultivation of mosses have been investigated for many years (Duckett et al, 2004;Hoffman, 1966;Sabovljevic et al, 2003); however, the mechanism of moss regeneration remains unclear.…”
Section: Y Guo and Y Zhao: Effects Of Storage Temperature On Desiccmentioning
confidence: 99%
“…The * symbol indicates a significant correlation at P < 0.05; * * indicates a significant correlation at P < 0.01. For more than a century, researchers have studied many aspects of mosses, such as inocula, pretreatment (e.g., storage and sterilization), culture methods, and culture conditions (Duckett et al, 2004;Hoffman, 1966). Some of these studies have implied that the physiological characteristics of moss gametophytes are closely related to the success of artificial cultivation; for example, pretreatment with sucrose and/or abscisic acid can improve the viability of mosses by increasing DT (Burch and Wilkinson, 2002).…”
Section: Relationships Between Physiological Characteristics and The mentioning
confidence: 99%
“…Thus, some researchers suggest artificially culturing moss biocrusts on degraded soil surfaces to accelerate the recovery of degraded arid and semiarid ecosystems (Belnap and Eldridge, 2003;Zhao et al, 2016). Recently, some mosses have been investigated by culturing gametophytes (Jones and Rosentreter, 2006;Xiao et al, 2015). However, cultivation research on moss crusts remains tentative, potentially due to the lack of knowledge regarding the vegetative propagation of mosses.…”
Section: Introductionmentioning
confidence: 99%